Orthogonal Experimental Research on Dielectrophoresis Polishing (DEPP) of Silicon Wafer - Zhao, Tianchen (Micromachines (Basel), 2020)
Silicon wafer with high surface quality is widely used as substrate materials in the fields of micromachines and microelectronics, so a high-efficiency and high-quality polishing method is urgently needed to meet its large demand. In this paper, a dielectrophoresis polishing (DEPP) method was proposed, which applied a non-uniform electric field to the polishing area to slow down the throw-out effect of centrifugal force, thereby achieving high-efficiency and high-quality polishing of silicon wafers. The principle of DEPP was described. Orthogonal experiments on important polishing process parameters were carried out. Contrast polishing experiments of silicon wafer were conducted. The orthogonal experimental results showed that the influence ratio of electric field intensity and rotation speed on material removal rate (MRR) and surface roughness was more than 80%. The optimal combination of process parameters was electric field intensity 450 V/mm, rotation speed 90 rpm, abrasive concentration 30 wt%, size of abrasive particle 80 nm. Contrast polishing experiments indicated that the MRR and material removal uniformity of DEPP were significantly better than traditional chemical mechanical polishing (CMP). Compared with the traditional CMP, the MRR of DEPP was increased by 17.6%, and the final surface roughness of silicon wafer reached Ra 0.31 nm. DEPP can achieve high-efficiency and high-quality processing of silicon wafer.